Features of building competitive programs in an acrobatic rock and roll in the boys category - Козаков [Michael Kоzakov] Михайло Валерійович (Slobozhanskyi Herald of Science and Sport, 2013)
The analysis of the competition program structure in the acrobatic rock and roll youth category finalists of European Championships in 2013 was carried out. The classification and drawing symbols of dance figures was developed. The most informative criteria for assessing of the program structure were defined: the total amount of dance figures, the ratio of dance figures in different sub-groups, the average dynamic index of a couple, the number of full competitive steps. We developed a method allowing to numerically define and compare the structures of couples’ competitive programs. Schematic analysis that determines the most efficient sequence in the development of a composition was carried out.